Investigation of direct Coagulation-Flocculation-Ultrafiltration (CFU) at lab-scale constant pressure and flux operation of copper removal - Sucipta Laksono; Ruth Butar; Sandyanto Adityosulindro (Sustinere: Journal of Environment and Sustainability, 2024)
Limited heavy metal concentrations in drinking water are harmful. The size-exclusion separation process was found to be a technology for removing heavy metals and organic substances. Although promising, a single ultrafiltration process is insufficient for the separation of heavy metals. Therefore, an additional process is required. The combination of coagulation flocculation followed by ultrafiltration was investigated. In this study, water matrix was used to simulate the worst-case scenario by adding 2 mg of copper to the surface water. For the filtration process, a comparison of single ultrafiltration with and without pretreatment using aluminum sulfate was investigated. Filtration was performed in a lab-scale experiment employing a polyethersulfone (PES) membrane with an average pore size of 30 nm operated at constant flux 120 L/m²⋅h and constant pressure of 0.7 bar. Furthermore, TDS retention, copper concentration, and turbidity were observed. Higher Cu removal was found at filtration under constant flux compared to constant pressure (81% and 66%, respectively. In the case of treated water with coagulation (optimum coagulation of 30 mg/L), higher removal of Cu was observed at constant flux operation compared to constant pressure, with 73% and 89% removal, respectively. Additional coagulation resulted in less membrane fouling during the filtration experiment, which explained the better performance almost double that of single ultrafiltration.